Hypoglycemia associated with ciprofloxacin use, a case report - Cestari, Matheus; Milano, Eduardo de Biasio; Capelli, Carolinne Cristina; Gudwin, Julia Freitas Leitão (Brazilian Journal of Implantology and Health Sciences, 2024)
Ciprofloxacin, a fluoroquinolone widely used for the treatment of bacterial infections, is associated with episodes of severe hypoglycemia. Although this condition is a class effect observed with various quinolones, ciprofloxacin is considered one of the lower-risk options, with a stronger correlation in the presence of other risk factors, particularly diabetes and the use of hypoglycemic medications. In the absence of these characteristics, its association is less prevalent. This paper aims to report the case of an elderly, non-diabetic patient not using hypoglycemic medications who developed episodes of hypoglycemia associated with ciprofloxacin use.